Carfilzomib for relapsed and refractory multiple myeloma - Groen, K (Cancer Manag Res, 2019)
Although the prognosis of multiple myeloma (MM) patients has dramatically improved during recent years, virtually all patients eventually develop relapsed refractory disease. Several new therapeutics have been developed in the last few years, including carfilzomib, a second-generation proteasome inhibitor (PI) that has been approved by the US Food and Drug Administration (FDA) in the setting of relapsed and/or refractory MM, as a single agent with or without dexamethasone, and in combination with lenalidomide in 2012 and 2015, respectively. Other promising combinations with carfilzomib are being investigated. Carfilzomib has shown superiority over the first-generation PI bortezomib on both efficacy and toxicity. In particular, profoundly lower incidence in polyneuropathy compared to bortezomib has been described. However, carfilzomib has a different toxicity profile, with more cardiovascular adverse events. Therefore, caution should be taken with the use of carfilzomib for elderly and cardiovascularly compromised patients. The once-weekly administration of carfilzomib, recently approved by the FDA in combination with dexamethasone, will lead to a lower burden for the patient and caregivers compared to the twice-weekly schemes that were routinely used until recently. This review has a focus on clinical trial data that has led to drug approval, as well as new promising combination studies, and provides advice for treating physicians who are now prescribing this drug to patients.